Inovasi dan Kreativitas Untuk Optimalisasi Pengolahan Nanas Khas Tangkit Jambi oleh Kube Mega Buana Melalui Pendampingan Teknologi dan Pemasaran Digital Berbasis Prinsip Ekonomi Syariah - Isnaeni, Nurida; Lubis, Paulina; Dean Amri, Ary; Zami Aprizal, Yusuf; Pratama, Aditya; Arfah, Arfah; Ramadhani Surya, Natasya (JPM MOCCI : Jurnal Pengabdian Masyarakat Ekonomi, Sosial Sains dan Sosial Humaniora, Koperasi, dan Kewirausahaan, 2025)
Innovation and creativity are the main keys in increasing the competitiveness of Tangkit Jambi's pineapple processing managed by KUBE Mega Buana. Through the use of appropriate technology and digital marketing strategies, various significant outputs have been achieved. Pineapple processed products are developed with new variants that are more innovative, accompanied by improved packaging quality so that they are able to meet modern market standards. The application of digital marketing based on social media and marketplaces has also expanded the distribution reach, which was originally limited to the local scope, now reaching regional markets. Furthermore, strengthening halal branding developed in accordance with sharia economic principles increases consumer confidence and provides added value to products. The increase in the capacity of KUBE members can be seen from skills in business management, technology utilization, and consistency in maintaining product quality. These results show that the integration of innovation, technology, and sharia values not only encourages the economic growth of business groups, but also strengthens the position of Tangkit pineapple as a regional leading commodity with wider development potential.